Bank regulatory capital and performance: evidence from Sub Saharan Africa - Yahaya, Adamu; Mahat, Fauziah; Matemilola, Bolaji Tunde (Statistical Economic and Social Research and Training Centre for Islamic Countries, 2020)
Continuous failure of banks witnessed across the Sub Saharan African region is a great source of concern among practitioners and society. The study seeks to evaluate the association between bank regulatory capital and performance. A panel of 50 public listed banks was drawn across 6 Sub Saharan African countries for a period of 9 years (2010-2018). This research paper makes use of the two-step system-generalized method of moment (GMM) as the most relevant technique of estimation due to its advantages of mitigating endogeneity problems and providing consistent estimates. The study found that bank regulatory capital has a positive significant association with performance. Moreover, the non-performing loan was found to have a negative significant association with bank performance. The results suggest that bank management should keep their non-performing loans at the barest minimal rate and ensure compliance with bank capital regulations.